Meaning in the Visual Arts - Panofsky, Erwin 1892-1968 (London Penguin Books, 1970)
Since its original publication, Erwin Panofsky's Meaning in the Visual Arts has been standard reading for students of art history. It is both an introduction to the study of art and, for those with more specialized interests, a profound discussion of art and life in the Middle Ages and Renaissance. Panofsky's historical technique reveals an abundance of detail, detail he skillfully relates to the life and work of individual painters and their times.The papers in this volume represent a cross-section of Panofsky's major work. Included are selections from his well-known Studies in Iconology and The Life and Art of Albrecht Dürer, plus an introduction and an epilogue?"The History of Art as a Humanistic Discipline" and "Three Decades of Art History in the United States: Impressions of a Transplanted European"?as well as pieces written especially for this collection. All display Panofsky's vast erudition and deep commitment to a humanistic conception of art and art history.